If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3 + 4x + 5 = 12 Reorder the terms: -3 + 5 + 6x + 4x = 12 Combine like terms: -3 + 5 = 2 2 + 6x + 4x = 12 Combine like terms: 6x + 4x = 10x 2 + 10x = 12 Solving 2 + 10x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 10x = 12 + -2 Combine like terms: 2 + -2 = 0 0 + 10x = 12 + -2 10x = 12 + -2 Combine like terms: 12 + -2 = 10 10x = 10 Divide each side by '10'. x = 1 Simplifying x = 1
| 0.5x-4=4 | | y=4x^2+3x^3 | | (x+2)(x-3)=x(x-2) | | 9-8c=-7 | | 219-2x=34x+23 | | 5h+7=177 | | x^3+3x^2-10x-42= | | 2x+1=x+2x+7 | | (x+12)(x+5)=(x-8)(x+7)-10 | | 1+3(6-6)+8= | | (x+5)(5-x)=(12+x)(4-x)+1 | | -20+6q=2 | | 12=20+2p | | 5x+3x-3y+4y= | | 24ab-2a+3-4ab= | | 3(2a+1)=11+4a | | 3(x-5)+2(x+1)=2 | | x^2+5-16=0 | | 3(x+1)=5x+7 | | x(x+2)=360 | | x+x^2=100 | | (x+y)(x^2-12xy-y^2)= | | 2+12x=122+x | | 3x^3-8x^2-60x=0 | | 2x+6=4-3x | | 4w^2-60w+200=400 | | 3ln(x)-ln(2)=4 | | 4w^2-60w+200=0 | | (x+1)(4x-3)=0 | | df=14 | | 3(z-2)=27 | | (q-5)x^2-4x-q=0 |